80.1k views
3 votes
Y=3x y=7x+16 systems of equations

User Artefacto
by
5.8k points

1 Answer

6 votes
Equation 1) y = 3x
Equation 2) y = 7x + 16

For both equations, move x to the left side, so that x and y are on the same side. To do so, subtract 3x from equation 1, and subtract 7x from equation 2.

So now, we have :

1) - 3x + y = 0
2) -7x + y = 16

Subtract equations from each other.

4x = -16

Divide both sides by 4.

x = -4

Plug in -4 for x in first equation.

y = 3x

y = 3(-4)

y = -12

(-4, -12)

~Hope I helped!~
User Kemen Paulos Plaza
by
5.9k points